MINAT MENGGUNAKAN DOMPET DIGITAL OVO DI KECAMATAN SUMBAWA DITINJAU MELALUI PERAN KEMUDAHAN, KEPERCAYAAN DAN KUALITAS LAYANAN - Sulistya, Irma; Fietroh, Muhammad Nur (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
The presence of Fintech forces people to innovate in terms of their financial transactions. This phenomenon is motivated by technological advances adapted by business people so that fintech players continue to innovate in providing the best for their users. OVO is one of the fintechs that is currently widely used by the public. This study aim to examine the effect of convenience, trust and quality of service on consumer interest in using the OVO digital wallet. The sampling technique used in this study was non probability sampling with a purposive sampling method. Non probability sampling is a sampling technique that does not provide an equal opportunity or chance for each element or member of the population to be selected as a sample. In this study, sampling was determined based on certain considerations or characteristics in accordance with research needs, so that the research sample consisted of 100 respondents from the community in Sumbawa Sub-District. The analysis technique used in this study was multiple linear regression. The results of this study showed that the convenience, trust and service quality have a positive and significant effect on consumer interest in using the OVO digital wallet at Sumbawa Sub-District. The influence of the variables convenience, trust and quality of service on consumer interest in using the OVO digital wallet at Sumbawa Sub District is 62.6%, while the remaining 37.4% is influenced by other variables outside this research model, such as perceived suitability, perception usefulness, perceived comfort and perceived feature availability.